2021
DOI: 10.3390/su132011207
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and Environmentally Sustainable Food Procurement and Foodservice in Australian Aged Care and Healthcare Services: A Scoping Review of Current Research and Training

Abstract: Balancing the adoption of environmentally sustainable food systems in Australian healthcare and aged care settings whilst meeting nutritional requirements has never been more critical. This scoping review aimed to identify: the major authoritative reports/guidelines related to healthy and environmentally sustainable food procurement and foodservice in aged care and healthcare services released by international and Australian governments/organizations; and the scope of healthy and environmentally sustainable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…This includes those already in the workforce, such as those in foodservice, dietetic and leadership positions. The limited opportunities specifically for nutrition professionals to learn about sustainability has been previously documented in the literature ( 17 , 18 ). Sustainable healthcare education develops students' knowledge, skills and attitudes about the interdependence of climate, ecosystems and health, as well as the healthcare sector's environmental impact and provides practical solutions to support ecosystems and human health ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…This includes those already in the workforce, such as those in foodservice, dietetic and leadership positions. The limited opportunities specifically for nutrition professionals to learn about sustainability has been previously documented in the literature ( 17 , 18 ). Sustainable healthcare education develops students' knowledge, skills and attitudes about the interdependence of climate, ecosystems and health, as well as the healthcare sector's environmental impact and provides practical solutions to support ecosystems and human health ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the need to decarbonise the entire health sector, 5 access to training regarding sustainability initiatives and opportunities remains limited. Focusing specifically on the training needs within hospital foodservices, staff both working in and managing these services require upskilling to apply evidence‐based approaches; however, a recent scoping review 42 identified that system‐wide training programmes are limited. This gap between recommendations to adopt environmentally sustainable practices and staff training remains a priority for action.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sustainable food procurement is about supporting local farmers and using environmentally friendly production methods. Opting for locally grown and seasonal produce not only reduces greenhouse gas emissions resulting from long transportation distances, but also promotes biodiversity conservation [25]. Nevertheless, the initial adoption of sustainable food systems may involve higher costs due to procurement changes and necessary staff training.…”
Section: Interplay Between Healthcare and Sustainable Food Systemsmentioning
confidence: 99%